Buenas prácticas de dispensación y satisfacción del servicio de farmacia en las Ipress I-3 y I-4 Maynas Ciudad Iquitos 2023 - Apagüeño Arévalo, Claudio Adriano (2024)
Good Dispensing Practices are necessary for adequate user satisfaction, which translates into effective and safe medication. The general objective of the research was to evaluate the good dispensing practices and satisfaction of the pharmacy service in IPRESS in Iquitos. Cross-sectional study that evaluated the Good Dispensing Practices of 11 IPRESS and 364 users of these establishments of the first level of care in a period of 6 months during the year 2024. The checklist for BPD validated by MINSA and a questionnaire on user satisfaction were applied. The data were analyzed with the SPSS v27 program. The results showed the IPRESS did not comply with Good Dispensing Practices and 91% user satisfaction. User satisfaction was significantly associated with 96% of users in pharmacy services with lower compliance with BPD compared to 89% of users in pharmacy services with higher compliance with BPD; pharmacy users with higher compliance with BPD show a lower need for improvement 71%, compared to 95% of users with lower compliance with BPD, however, they have a higher percentage of users 86% who are not completely satisfied with the care or do not consider it excellent. We conclude that there is a relationship between Good Dispensing Practices and user satisfaction in the IPRESS evaluated.